2013
DOI: 10.1016/j.jcdr.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of cardiovascular risk factors among policemen in Puducherry, South India

Abstract: a b s t r a c tBackground: Diabetes mellitus and hypertension (HT) are common diseases in adulthood, pre-disposing to many cardiovascular complications, posing a major public health challenge. Few studies have reported increased prevalence of cardiovascular disease risk factors and type 2 diabetes in policemen. Hence, this study aims to assess the prevalence of cardiovascular risk factors such as diabetes, HT, smoking, alcohol intake, and obesity among policemen. Materials and methods: A cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
42
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 17 publications
15
42
7
Order By: Relevance
“…Our results support earlier research of police officers suffering from stress due to their occupation. 9 Similar occupational stress prevalence and stressors were found in study conducted in Wardha 10 and Puduchery 11 . Some studies also reported that Police personnel are under continuous and constant stress due to similar stressors that lead to psychiatric morbidity.…”
Section: Discussionsupporting
confidence: 68%
“…Our results support earlier research of police officers suffering from stress due to their occupation. 9 Similar occupational stress prevalence and stressors were found in study conducted in Wardha 10 and Puduchery 11 . Some studies also reported that Police personnel are under continuous and constant stress due to similar stressors that lead to psychiatric morbidity.…”
Section: Discussionsupporting
confidence: 68%
“…18 However the studies conducted by Tharkar et al 19 from Chennai and Ramakrishnan et al 20 from Puducherry reported a higher prevalence of diabetes among police personnel, 32% and33.6% respectively compared to the present study (8.3%).…”
Section: Discussioncontrasting
confidence: 65%
“…In the present study, the prevalence of hypertension was 8.3% as compared to 30.5%and 58.5% in the studies conducted by Ramakrishnan et al 20 and Shabana et al 19 respectively. The higher prevalence may be due to the difference in age distribution; our study comparatively had younger police personnel than the other studies.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…6 Hypertension is defined as a systolic BP of 140 mmHg or above or diastolic BP of 90 mmHg or above, in a minimum of 2 readings at least 5 minutes apart. The subjects were classified as Normal, Pre-hypertensive or Hypertensive according to JNC VII criteria.…”
Section: Study Tools and Methods Of Data Collectionmentioning
confidence: 99%